Innovative mechanisms of modernization of system of local state management in the Republic Kazakhstan (Journal of Economic Research & Business Administration, 2016)
Article is devoted to the reform of the system of local governance through the introduction of innovative management techniques. Need of development of new administrative ideology, initiation of new adminis-trative processes, change of administrative structures is proved that puts before the modern theory and practice of a state administration a problem of complex innovative reforming of system of the state management taking into account national features of each country.
Keywords: local public administration; innovative technologies; mod-ernization; public management; interaction of state agencies.